![image](https://tex.z-dn.net/?f=lim_%7Bx-%3E7%7D+%5Cfrac%7B%5Csqrt%7B2%2Bx%7D-3%7D%7Bx-7%7D%3D%7C%5Cfrac%7B0%7D%7B0%7D%7C%3D%5C%5C%5C%5Clim_%7Bx-%3E7%7D+%5Cfrac%7B%5Csqrt%7B2%2Bx%7D-3%7D%7B2%2Bx-9%7D%3D%5C%5C%5C%5Clim_%7Bx-%3E7%7D+%5Cfrac%7B%5Csqrt%7B2%2Bx%7D-3%7D%7B%28%5Csqrt%7B2%2Bx%7D%29%5E2-3%5E2%7D%3D%5C%5C%5C%5Clim_%7Bx-%3E7%7D+%5Cfrac%7B%5Csqrt%7B2%2Bx%7D-3%7D%7B%28%5Csqrt%7B2%2Bx%7D-3%29%28%5Csqrt%7B2%2Bx%7D%2B3%29%7D%3D%5C%5C%5C%5Clim_%7Bx-%3E7%7D+%5Cfrac%7B1%7D%7B%5Csqrt%7B2%2Bx%7D%2B3%7D%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B2%2B7%7D%2B3%7D%3D%5Cfrac%7B1%7D%7B%5Csqrt%7B9%7D%2B3%7D%3D%5Cfrac%7B1%7D%7B3%2B3%7D%3D%5C%5C%5C%5C%5Cfrac%7B1%7D%7B6%7D)
7} \frac{\sqrt{2+x}-3}{x-7}=|\frac{0}{0}|=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{2+x-9}=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{(\sqrt{2+x})^2-3^2}=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{(\sqrt{2+x}-3)(\sqrt{2+x}+3)}=\\\\lim_{x->7} \frac{1}{\sqrt{2+x}+3}=\frac{1}{\sqrt{2+7}+3}=\frac{1}{\sqrt{9}+3}=\frac{1}{3+3}=\\\\\frac{1}{6}" alt="lim_{x->7} \frac{\sqrt{2+x}-3}{x-7}=|\frac{0}{0}|=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{2+x-9}=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{(\sqrt{2+x})^2-3^2}=\\\\lim_{x->7} \frac{\sqrt{2+x}-3}{(\sqrt{2+x}-3)(\sqrt{2+x}+3)}=\\\\lim_{x->7} \frac{1}{\sqrt{2+x}+3}=\frac{1}{\sqrt{2+7}+3}=\frac{1}{\sqrt{9}+3}=\frac{1}{3+3}=\\\\\frac{1}{6}" align="absmiddle" class="latex-formula">
-----------------
![image](https://tex.z-dn.net/?f=lim_%7Bx-%5Cinfty%7D+%5Cfrac%7B-8%2Bx%5E3%7D%7B18%2Bx%5E3%7D%3D%7C%5Cfrac%7B%5Cinfty%7D%7B%5Cinfty%7D%7C%3D%5C%5C%5C%5Clim_%7Bx-%3E%5Cinfty%7D+%5Cfrac%7B-%5Cfrac%7B8%7D%7Bx%5E3%7D%2B1%7D%7B%5Cfrac%7B18%7D%7Bx%5E3%7D%2B1%7D%3D%5Cfrac%7B0%2B1%7D%7B0%2B1%7D%3D1)
\infty} \frac{-\frac{8}{x^3}+1}{\frac{18}{x^3}+1}=\frac{0+1}{0+1}=1" alt="lim_{x-\infty} \frac{-8+x^3}{18+x^3}=|\frac{\infty}{\infty}|=\\\\lim_{x->\infty} \frac{-\frac{8}{x^3}+1}{\frac{18}{x^3}+1}=\frac{0+1}{0+1}=1" align="absmiddle" class="latex-formula">